Emergence and genomic analysis of a novel sublineage of bovine ephemeral fever virus in Southwest China - Chen, Jing; Liu, Mengru; Li, Yixuan; Yang, Liu; Tang, Yunhan; Dan, Ruitong; Xie, Muhan; Fang, Rendong; Li, Nengzhang; Ye, Chao; Peng, Yuanyi (Frontiers in Microbiology, 2023)
Bovine ephemeral fever virus (BEFV), belonging to the genus Ephemerovirus under the family Rhabdoviridae, is the aetiological cause for the bovine ephemeral fever (BEF) in cattle and water buffalo. In this study, we report recent BEF outbreaks in Southwest China and sequence the complete genome sequence of one BEFV isolate BEFV/CQ1/2022. Comparative genomic analyses between BEFV/CQ1/2022 and isolates available in GenBank revealed remarkable inter-isolate divergence. Meanwhile, the sequence divergence was related to the evolutionary relationships and geographical distribution of the isolates. Phylogenetic analysis indicated that the global BEFV isolates can be divided into 4 distinct lineages. The East Asia lineage was the most diverse and could be subdivided into 4 sublineages. Notably, BEFV/CQ1/2022 and other 10 recent isolates from Mainland China were found to be clustered in sublineage 2. Additionally, recombination analysis provided evidence of BEFV recombination among East Asian isolates for the first time. Taken together, a novel sublineage of the East Asian BEFV emerged in Southwest China, and large divergence and potential recombination among BEFV strains were investigated in this study, which may improve understanding of BEFV epidemiology and evolution.